Supporting community seedbanks to realize farmers’ rights - Clancy, Evelyn (2016)
Support of community seedbanks and seed-savers groups throughout the world can contribute to the empowerment of men and women farmers, encourage ecological citizenship and responsibility towards agrobiodiversity and promote resilience of farming communities. This can lead to sustainable livelihoods, food sovereignty, sustainable use of plant genetic resources for food and agriculture and food security. To achieve this, farming communities, research organizations and government institutions should work together while acknowledging the challenges related to governance, in terms of technical, social and political issues and the legal environment. The realization of farmers’ rights is one these challenges. A global platform is proposed as a supportive mechanism towards formally recognizing and supporting community seedbanks. The support of national governments and the International Treaty on Plant Genetic Resources for Food and Agriculture will be important for such a platform.